2020
DOI: 10.1158/1535-7163.mct-19-1021
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based MAPK Reporter Assay Reveals Synergistic MAPK Pathway Activity Suppression by MAPK Inhibitor Combination in BRAF-Driven Pediatric Low-Grade Glioma Cells

Abstract: Pilocytic astrocytomas (PAs) as well as other pediatric low-grade gliomas (pLGGs) exhibit genetic events leading to aberrant activation of the MAPK pathway. The most common alterations are KIAA1549:BRAF fusions, BRAF V600E and NF1 mutations. Novel drugs targeting the MAPK pathway (MAPKi) are prime candidates for the treatment of these singlepathway diseases. We aimed to develop an assay suitable for pre-clinical testing of MAPKi in pLGGs with the goal to identify novel MAPK pathway suppressing synergistic drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In contrast, the effect of trametinib alone in the short-term exposure experiment showed IC 50 values exceeding 10 µM. Interestingly, in the MAPK pathway-activated pLGG IC 50 values for trametinib are in the low nm range suggesting activation of alternative pathways such as mTOR in fusion-positive pHGG [ 44 ]. Moreover, in the long-term exposure, already 1 µM of trametinib led to a distinct decrease in cell viability and markedly exceeded the effect of entrectinib alone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of trametinib alone in the short-term exposure experiment showed IC 50 values exceeding 10 µM. Interestingly, in the MAPK pathway-activated pLGG IC 50 values for trametinib are in the low nm range suggesting activation of alternative pathways such as mTOR in fusion-positive pHGG [ 44 ]. Moreover, in the long-term exposure, already 1 µM of trametinib led to a distinct decrease in cell viability and markedly exceeded the effect of entrectinib alone.…”
Section: Discussionmentioning
confidence: 99%
“…The universal activation of the MAPK pathway makes pLGGs uniquely suited for targeted treatment approaches. Pre-clinical data points to robust inhibition of the MAPK pathway by MEK inhibitors (MEKi) such as selumetinib and trametinib in pLGG cells with KIAA1549:BRAF-fusion or BRAF V600E mutation [15,16]. Selumetinib has been studied in a series of clinical trials: 20% of patients with recurrent or progressive pLGG showed sustained partial response in a phase I clinical trial [17] and 36-40% of progressive pLGG patients experienced a sustained partial response in a phase II trial [18].…”
Section: Introductionmentioning
confidence: 99%
“…This intracellular functionality was utilised to screen the SH2 A mer toolbox in a pERK translocation assay. Popular methods for investigating MAPK signalling include western blotting and SRE luciferase assays, which can be slow and labour intensive [39] so high-content imaging was used together with GFP-tagged SH2-binding A mer constructs yielding a simple, time e cient and sensitive assay. This approach is easily modi ed to screen different endpoints, for example modulation of the phosphatidylinositol 3-kinase (PI3K)/AKT pathway by using AKT phosphorylation as the measurable endpoint [40], or any other phenotypic change that can be imaged or measured.…”
Section: Discussionmentioning
confidence: 99%